Catalog of Hymenoptera described by Giovanni Gribodo (1846–1924) (Insecta) - Penati, Fabio; Mariotti, Alberto (Zootaxa, 2015)
Giovanni Gribodo (1846–1924) was an Italian civil engineer who described 377 new taxa of Hymenoptera, 199 of which are still valid and in use today, and proposed 6 replacement names. The present catalog provides a brief biography of Gribodo, a bibliography of his 42 publications and a complete list of the taxa proposed by Gribodo. The catalog lists, for all published names, details on the type series, type locality and collector, present status based on literature, all data labels, relevant references and remarks. A gazetteer of type-localities, a systematical list of Genus- and Species-group names, a chronological list of new names proposed by Giovanni Gribodo, with name-bearing types, and a list of Algerian species and varieties are also given. Furthermore, an unpublished manuscript by Gribodo on hymenopterological fauna of Tunisia, still kept at the Civic Museum of Natural History “Giacomo Doria” (Genoa, Italy), is described, and data on the 57 “new” taxa therein listed are reported, discussing their relevance in order to ascertain the original type series of 27 taxa validly published later. Finally, the problem posed by the enigmatic “disappearance” of a large number of Algerian types, already faced by several entomologists in the past, is analyzed, in order to prevent future mistaken designations of lectotypes and neotypes.        The following six nomenclatural acts are proposed here by R. Wahis: Hemipepsis sycophanta Gribodo, 1884 = Hemipepsis bellicosa (Smith, 1873) new synonym; Anospilus sulcithorax (Gribodo, 1924) new combination; Auplopus validus (Gribodo, 1884) new combination; Dichragenia quartinae (Gribodo, 1884) new combination; Diplonyx caesar (Gribobo, 1894) new combination; Paracyphononyx melanicrus Gribodo, 1884 status revalidated (resurrected from synonymy with Pompilus ruficrus Klug, 1834).        The following four nomenclatural acts are proposed by F. Penati: Parachrysis Gribodo, 1879 [subgenus of Chrysis Linnaeus] = Chrysis Linnaeus, 1760 new synonym; Psammotherma (Mutilla) quartinae Gribodo, 1884 = Psammotherma flabellata (Fabricius, 1804) new synonym; Megascolia (Regiscolia) alecto (Smith, 1858) subspecies vespillo (Gribodo, 1893) new combination; Megachile (Megachile) moutoni Gribodo, 1894 emendated name.